Misconceptions: How To Diagnose And Clarify Them In Undergraduate Medical Students - Sara Shakil (Journal of Bahria University Medical and Dental College, 2015)
ABSTRACT: A big challenge for medical educationists is to search for learning strategies that promote meaningful learning and discourage rote learning. Clinical expertise is achieved by acquiring large amounts of biomedical knowledge structured as concepts linked together in a loosely connected semantic network. Medical students using concepts maps can successfully retrieve information in the short term. Concept maps allow students to recognize the relationship between concepts, which reflects the kind of real-world thinking predominant in the clinical setting. Conceptual thinking occurs when a student goes beyond the surface structure of a problem and recognizes how the problem can be solved, and in addition, possesses the content knowledge integral to solve the problem. Without both components a student may not just be able to critically analyze one problem, but will also fail when given a similar problem in a different context. Hence, there is great need for identification of these learning difficulties mainly in the form of confusions, ambiguities and misconceptions in the learner’s mind.